Sosialisasi Peningkatan Kesadaran Santri terhadap Tindakan Perundungan di Lingkungan Pondok Pesantren Darul Amin - Thohir, Moh (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Islamic boarding schools are Islamic educational institutions that aim to understand, appreciate, and practice the teachings of Islam by emphasizing the importance of religious morals as guidelines in everyday social life. In pesantren, students are expected to apply good values in interactions with fellow students. However, the understanding of the impact of bullying is still unclear for some students. Bullying behavior often occurs unconsciously as part of social interaction, for example, teasing which is initially considered a joke, but then develops into a serious problem. Through this counseling, it is hoped that students can better understand the negative impacts that may arise due to bullying. The method of implementing this community service is in the form of counseling with slide presentation media and infocus, which was conducted at one of the Islamic Boarding Schools in South Tangerang. During the education process, pesantren also face various problems, one of which is bullying which often occurs due to lack of supervision from the pesantren. With this counseling, it is hoped that students will be more aware and understand the bad consequences of bullying.